2021
DOI: 10.1186/s12885-021-08306-5
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Somatostatin analogues for neuroendocrine tumor patients: a cost-effectiveness analysis

Abstract: Background & Aims Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are heterogeneous neoplasms. Although some have a relatively benign and indolent natural history, others can be aggressive and ultimately fatal. Somatostatin analogues (SSAs) improve both quality of life and survival for these patients once they develop metastatic disease. However, these drugs are costly and their cost-effectiveness is not known. Methods A decision-analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We identified systemic therapy, specifically somatostatin analogs, as the primary driver of high cost in this population of patients, in line with findings from previous studies from other countries. [24][25][26] Our study adds to the growing body of literature 21,24,26,28 that supports careful consideration of limiting the upfront use of somatostatin analogs, particularly in patients with low-grade disease, to optimize high value care. Future studies using this methodology should incorporate the cost of PRRT to reflect the current state of metastatic NEN treatment, study the impact of insurance type on the CCPD and survival, and aim to capture costs at other institutions or health care systems for comparison to identify best practices for delivering highvalue care.…”
Section: Discussionmentioning
confidence: 62%
“…We identified systemic therapy, specifically somatostatin analogs, as the primary driver of high cost in this population of patients, in line with findings from previous studies from other countries. [24][25][26] Our study adds to the growing body of literature 21,24,26,28 that supports careful consideration of limiting the upfront use of somatostatin analogs, particularly in patients with low-grade disease, to optimize high value care. Future studies using this methodology should incorporate the cost of PRRT to reflect the current state of metastatic NEN treatment, study the impact of insurance type on the CCPD and survival, and aim to capture costs at other institutions or health care systems for comparison to identify best practices for delivering highvalue care.…”
Section: Discussionmentioning
confidence: 62%
“…Several analyses have shown that RLT is a cost-effective alternative to systemic treatment in other cancers such as neuroendocrine tumors. [25][26][27][28] In the diagnostic process, the proPSMA trial has shown the superior diagnostic value of 68 Ga-PSMA-PET compared with conventional imaging in patients with prostate cancer, and it has also proved to be less costly. 29 Besides primary staging, the early detection of metastasis also has a high value in recurrent disease, such as in the setting of oligometastatic disease 30 and in differentiating nonmetastatic from metastatic prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although SSA discontinuation for high-grade toxicity is rare, the incidence of low-grade toxicity is significant ( Sorbye et al 2020 ), with adverse events in prospective trials ranging from 31 to 51% ( Caplin et al 2014 , Wolin et al 2015 , Strosberg et al 2017 , Pavel et al 2021 ). Two recent cost-effectiveness analyses (representative of US prices) showed a high cost per quality-adjusted life year in some situations and are indicative of the financial burden of SSA treatment ( Joish et al 2018 , Rustgi et al 2021 ). We thus examined whether lower SSA doses might be equally effective.…”
Section: Discussionmentioning
confidence: 99%